Delegating work : match skills with tasks, develop your people, overcome barriers. (Boston, Massachusetts : Harvard Business Review Press, 2014)
Walks you through the fundamentals of establishing a productive environment, assigning the right work to the right people, conducting an effective hand-off meeting, and monitoring without micromanaging.
Why delegate? -- Building a foundation for effective delegatng -- Preparing to delegate -- Making the assignment -- Monitoring the assignment -- Review the process.
Includes bibliographical references and index.
Keywords: Delegation of authority; Workflow -- Management; Management; Delegation of authority; Management; Workflow -- Management